HERALD OF DESTINY THE POLITICAL PHILOSOPHY OF ANTENOR ORREGO - Rivera, Victor (2005)
This article aims to show Orrego's philosophy as a whole consruct. Sorneconcepts like "rationality", "heroe" and "destiny" are underlined with thepurpose of grasping the meaning and significance of his work. Notignoring historical sources, Orrego is inscribed into current debate onpractica! rationality.